2009
DOI: 10.1158/1055-9965.epi-08-1186
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Carcinoma and Sexual Behavior: Collaborative Reanalysis of Individual Data on 15,461 Women with Cervical Carcinoma and 29,164 Women without Cervical Carcinoma from 21 Epidemiological Studies

Abstract: High-risk human papillomavirus (HPV) types cause most cervical carcinomas and are sexually transmitted. Sexual behavior therefore affects HPV exposure and its cancer sequelae. The International Collaboration of Epidemiological Studies of Cervical Cancer has combined data on lifetime number of sexual partners and age at first sexual intercourse from 21 studies, or groups of studies, including 10,773 women with invasive cervical carcinoma, 4,688 women with cervical intraepithelial neoplasia grade 3 (CIN3)/carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(23 citation statements)
references
References 67 publications
1
20
0
2
Order By: Relevance
“…Cervical squamous cell carcinoma risk is 1.5 times higher in current smokers than in people who have never smoked [14]. Cervical cancer risk is almost three times higher in women who had 6 or more sexual partners, compared to those who had only one [15]. [17].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Cervical squamous cell carcinoma risk is 1.5 times higher in current smokers than in people who have never smoked [14]. Cervical cancer risk is almost three times higher in women who had 6 or more sexual partners, compared to those who had only one [15]. [17].…”
Section: Discussionmentioning
confidence: 94%
“…However, many young women become infected with multiple types of human papilloma virus, which then can increase their risk of getting cervical cancer in the future. Early age at first intercourse is consistently found to be a risk factor in most of the early epidemiological studies of cervical cancer [15] [20]. Cervical cancer risk is double in women who first had sexual intercourse at the age of 14 or less, compared to those who did at 25 or more [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pooled analysis of international case-control studies found that smoking was associated with similar 2-fold greater odds of both carcinoma in situ and invasive cervical cancer among HPV positive women, and found no evidence of age-group differences in the effects of smoking with invasive and in situ cases combined(24). Our selection of candidate cofactors for CIN3+ was informed by the larger body of literature on invasive cervical cancer, which has identified associations with age at first full-term pregnancy and number of full-term pregnancies(23), lifetime number of sexual partners(25), hormonal contraceptive use(26), and smoking (24, 27). It is important to consider cofactors for CIN3+ because precancerous lesions are the target of screening activities, and cofactors for this endpoint might differ from those for invasive cancers because of the timing of exposures, the portion of the pathophysiologic process affected by the risk factor, the age of cases, or differences in control selection.…”
Section: Discussonmentioning
confidence: 99%
“…2 Early age at first sexual intercourse (AFI) is an important risk factor for cervical cancer. 3 Other risk factors include lifetime number of sexual partners, 4 tobacco use 5 hormonal contraceptives, 6 young age at first full-term pregnancy and number of full-term pregnancies. 7 …”
Section: Introductionmentioning
confidence: 99%